Pengaruh Kualitas Konten Pada Akun Instagram @Folkative Terhadap Minat Baca Pada Kalangan Generasi Z - Azis, Muhammad Abdul; Dharta, Firdaus Yuni; Oxcygentri, Oky (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to examine the influence of content quality on the Instagram account @folkative toward reading interest among Generation Z. Known for their high engagement with social media and preference for visual-informative content, Generation Z serves as the focus of this quantitative research. The study involved 100 respondents aged 17–27 who follow the @folkative account. Data were collected through questionnaires and analyzed for validity and reliability. The findings reveal that content quality—covering accuracy, relevance, depth, and presentation style—has a significant impact on the reading interest of Generation Z. The results indicate that well-crafted and informative social media content can effectively increase young audiences’ interest in reading. This study offers practical insights for digital media managers to design more engaging content strategies that promote literacy in the digital age.